Pelatihan Entrepreneurship untuk Menumbuhkan Jiwa Berwirausaha pada Siswa/i SMK Negeri 1 Kabanjahe - Pertiwi, Suci; Yolanda, Yola; Tarigan, Purnaya Sari (Universitas Methodist Indonesia, 2024)
Entrepreneurship has become one of the main drivers of economic growth and social development in various countries. The ability of individuals to create, develop and manage their own businesses has opened up new opportunities for inclusive economic development. In Indonesia, the entrepreneurship sector is increasingly being considered as a way to reduce unemployment, improve community welfare and encourage innovation. The development of the creative economy cannot be separated from the young generation as a repository of creativity, namely that their creative ideas in entrepreneurship can help the government in its efforts to reduce the unemployment rate in Indonesia [1]. The partner's problem is the lack of knowledge related to entrepreneurship and the low interest in entrepreneurship among students in SMK Negeri 1 Kabanjahe. The solution we offer in this service is to provide knowledge about Entrepreneurship, especially to students who are still in class XI vocational school, with a focus on developing business ideas, business planning and implementation skills. We believe that investing in increasing entrepreneurial understanding and related skills will help create future leaders who are able to innovate, create jobs, and contribute to sustainable economic growth